A mixed molecular salt of lithium and sodium breaks the Hume-Rothery rules for solid solutions. Issue 16 (4th February 2019) - Lestari, Monica; Lusi, Matteo
Abstract : Despite the difference in size and chemistry, lithium and sodium form a solid solution as isoorotate salt. Such behaviour, which represents an exception to the Hume-Rothery rules, can be exploited in the preparation of novel lithium drugs. Abstract : The first molecular solid solution of lithium and sodium ions is reported. In spite of the different chemical and structural properties of the parent compounds, the two cations form a homogeneous mixed phase with the isoorotate ion. Such observation appears in contrast with the Hume-Rothery principles for solid solutions. Furthermore the mixed salts in the series are thermally stable up to 100 °C and non-hygroscopic, which makes them relevant for their potential use as a lithium drug substance.